The low temperatures of the air in winter in West Kazakhstan (Journal of Geography and Environmental Management, 2016)
The low temperature rate of the air in winter in West Kazakhstan is considered. Data on average monthly temperature for 1971-2000 and absolute minimum temperatures of the air for December, January and February at six meteorological stations (MS) relatively even located on the territory under discussion are the initial material to do research. The average number of days with hard frost is calculated. The day with hard frost is considered to be the case when minimum temperature of the air at least in one of the periods during 24 hours decreases to 25 ˚C or lower. Absolute minimum of the air temperature is also considered as the value characterizing climatic peculiarities of the low temperature distribution of the air on the territory under study. The lowest air temperatures (from minus 34 to minus 48 ˚C) were observed in the last century. To evaluate the degree of territory embracing by the air temperature anomaly of one sign, ρ parameter is calculated. The months and years are singled out when positive or negative anomalies predominate on the territory under research. The time period of the average monthly temperature is studied. The linear trend coefficient has negative value in December, the temperature decreases 0.3-0.5 ˚C/10 years on average and only at MS Zhalpaktal a weak positive trend is observed (0.1 ˚C/10 years). In January and February the tendency of increasing the air temperature by 0.15-0.23 ˚C/10 years throughout the territory is observed. Two parameters: N.A.Bagrov’s index and the value of average quadratic deflection are used to single out months with large anomalies of the air temperature. N.A.Bagrov’s index gives integral evaluation of the field anomaly degree of the air temperature. Maximum values of the index were recorded in December 1984, January 1972 and February 1994. These months were the coldest months in West Kazakhstan when average anomaly value of the air temperature was minus 7.6˚, minus 11.0˚ and minus 8.2˚ respectively. The catalogue of extremely cold winter months is compiled: 4 cases in December, 7 cases in January and 4 cases in February. The values of the temperature anomaly for these months are cited.
Keywords: average monthly air temperature